Inspection of air conditioning systems - Hitchin, Roger (CIBSE, 2012)
CIBSE TM44 is used as the guidance for air conditioning inspections in the UK, the Republic of Ireland, Malta and Gibraltar. The guidance is primarily intended to support inspections which are carried out for compliance with the EPBD, but will also be useful to anyone who wishes to assess the energy effi ciency of an air conditioning system. With the benefit of the experience gained over the past three years, and to clarify some of the questions about air conditioning system inspections that have arisen over that period, the TM has been revised. The revision also takes into account the reporting templates produced by the Department for Communities and Local Government for the production of reports in England and Wales. These templates will also form the basis for statutory lodgement of air conditioning inspection reports, which will be required in England and Wales as from 6th April 2012 under amendments to the Energy Performance of Buildings Regulations 2007. The revision has also provided the opportunity to incorporate the separate legislative requirements for Northern Ireland and Scotland in the main text of the TM, rather than as separate addenda. TM44 provides guidance on conducting an air conditioning inspection to satisfy the requirements of the Directive as expressed in the various regulations in the UK. The focus is on systems that use refrigerants to produce cooling. Some of the guidance may also be applicable to elements of other forms of cooling systems, such as those that use pipes or ducts built into the fabric of the building (e.g. cooled deck or ceiling slabs), or those which use aquifers or local water sources to provide cooling solutions. TM44: 2007 is superseded by this new edition.
Keywords: Air conditioning -- Inspection.; Air conditioning -- Safety regulations.; Air conditioning -- Equipment and supplies -- Maintenance and repair.; elektronické knihy; electronic books